Carbohydrate‐Based Polymer Brushes Prevent Viral Adsorption on Electrostatically Heterogeneous Interfaces. Issue 1 (15th October 2018) - Kumar, Ramya; Kratzer, Domenic; Cheng, Kenneth; Prisby, Julia; Sugai, James; Giannobile, William V.; Lahann, Joerg
Abstract: Chemical heterogeneity on biomaterial surfaces can transform its interfacial properties, rendering nanoscale heterogeneity profoundly consequential during bioadhesion. To examine the role played by chemical heterogeneity in the adsorption of viruses on synthetic surfaces, a range of novel coatings is developed wherein a tunable mixture of electrostatic tethers for viral binding, and carbohydrate brushes, bearing pendant α‐mannose, β‐galactose, or β‐glucose groups, is incorporated. The effects of binding site density, brush composition, and brush architecture on viral adsorption, with the goal of formulating design specifications for virus‐resistant coatings are experimentally evaluated. It is concluded that virus‐coating interactions are shaped by the interplay between brush architecture and binding site density, after quantifying the adsorption of adenoviruses, influenza, and fibrinogen on a library of carbohydrate brushes co‐immobilized with different ratios of binding sites. These insights will be of utility in guiding the design of polymer coatings in realistic settings where they will be populated with defects. Abstract : A tunable coating comprising nonfouling carbohydrate brushes and electrostatic binding sites for viruses is employed to study the relationship between surface design parameters and viral adsorption . Ultimately, brush architecture determines whether the binding sites are exposed to, or shielded from viruses. These insights will guide the design of polymer coatings that can resist viral binding despite being populated with defects.